Reconstruction of the mandible following benign tumor ablations: An audit of 20 cases. Issue 5 (September 2015) - Akinbami, Babatunde O.; Akadiri, Oladimeji A.
Abstract: Objectives: Resections of benign tumors of the mandible result in continuity defects of varying span which can be reconstructed with either vascularized bone graft or non-vascularized bone graft with or without alloplastic materials. We documented the morbidities and outcomes of reconstructions of extensive defects of the mandible in a tertiary health center. Methods: All consecutive patients were included. The extents of mandibular involvement were classified. Morbidities at both sites and take of grafts were assessed by clinical examinations and radiographic evaluation. Results: A total of 20 patients with equal gender distribution were evaluated. Age range was 10–54 years, mean (SD) of 24.3 (10.9). Sixteen (80%) patients had ameloblastoma, and 2 (10%) keratocystic odontogenic tumor. Primary reconstruction with both autograft and alloplast was done in 14 (70%) patients and primary reconstruction with iliac bone graft in 6 (30%). The extent of mandible involvement was limited to one side of the bone in 2 (10%) patients. It crossed midline in 8 (40%) and it involved both sides of the bone in 8 (40%) patients. Conclusion: We had 65% success rate. To avoid the long operation time and cost of using vascularized grafts, we recommend that non-vascularized grafts are very useful in the reconstruction of intermediate to long span mandible defect.